Analysis of Factors Affecting Demand Subsided House in East Lombok District - Arina Maulida; Emi Salmah; Eka Agustiani (Experimental Student Experiences, 2022)
This study aims to determine whether income, price, facilities and location have a significant effect on the demand for subsidized housing in East Lombok District, a case study in Selong District. As well as to find out whether income, price, location and facilities together have a significant effect on the demand for subsidized housing in East Lombok Regency. Case study in Selong District. This study uses an analytical tool in the form of multiple linear regression analysis. And from the results of the research, the regression equation is obtained as follows Y = 2.932 + 0.096 (X1) + 0.431 (X2) – 0.192 (X3) + 0.528 (X4) + ei. Where the location variable gives the greatest and positive influence followed by price and income variables, while the facilities variable gives a negative value. When viewed from the magnitude of the coefficient of determination (adjusted R square) it has a positive value of 0.259 which indicates the variability of the dependent variable can be explained by the independent variable of 25.9% and another explanation of 74.1% is explained by other variables that are not contained in the model and or not observed in this study.